Changes in the Production of Certain Proinflammatory Cytokines in Patients with Various Variants of Coronary Heart Disease - Mirzo K. Mirzaev; Aziz X. Urokov; Eleanora N. Tashkenbaeva (Zien Journals, 2022)
To date, it is the inflammatory process that is considered as one of the main links in the pathogenesis, clinic and prognosis of coronary heart disease. He also plays a significant role in the occurrence and subsequent development of acute myocardial infarction and the outcome of the disease, namely in the formation of atherothrombosis, alteration, necrosis and repair with further remodeling of the myocardium of the heart. Given that the prognosis of myocardial infarction is determined by both the degree of myocardial damage and complications arising during various periods of the disease, primarily cardiovascular insufficiency, studies aimed at identifying indicators that can be used in practice to predict and prevent the development of complications of myocardial infarction, determining the tactics of their treatment, are of particular relevance
Keywords: myocardial infarction; coronary heart disease